The Effect of SCMs on the Resistance of Steam-cured Concrete to Chloride Attack in the Tidal Zone of Real Marine Environment - Sun, Xiaoguang; Wang, Penggang; Du, Zhenxing; Han, Xiaofeng; Zhao, Lixiao; Tian, Li (Journal of Advanced Concrete Technology, 2024)
Steam curing is a widely used technique for producing precast concrete components in practical engineering. Chloride attack is a main factor that leads to the corrosion of rebars in concrete structures, which significantly affects the durability and safety of concrete structures in marine environments. In this paper, XRD, LF-NMR, 29Si NMR, and 27Al NMR were used to investigate the microstructure evolution of steam-cured concrete and standard-cured concrete. Then, the steam-cured and standard-cured concrete were subjected to actual marine exposure tests to explore the microstructure evolution of concrete and the chloride erosion behavior in the tidal zone. The results showed that steam-curing can increase the average molecular chain length (MCL) and polymerization degree of C-(A)-S-H, promote the transformation of silicon-oxygen tetrahedral dimer to polymer, and increase the Q2/Q1 value of steam-cured concrete to twice that of standard-cured concrete. Compared to standard-cured specimens, steam-cured concrete specimens had significantly more harmful pores and multi-harmful pores. With the increase of exposure time to the marine environment, the depth of the convection zone inside the concrete did not change significantly, however, the peak value of chloride concentration increased gradually. The addition of SCMs to steam-cured concrete reduced the content of free and total chloride, which was well explained by microscopic tests. The concentration of chloride on the surface and chloride diffusion coefficient of steam-cured concrete showed a quadratic function relationship with the increase of slag content, and an exponential decay relationship with the content of fly ash.